2020
DOI: 10.1186/s12885-020-07431-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity and lymphoma: a systematic review and meta analysis

Abstract: Background The literature suggests an increased risk between anthropometrics including higher body mass index and lymphoma incidence; however, the association with physical activity remains unclear. A systematic review/meta-analysis was therefore performed to examine this association with physical activity (total, recreational or occupational). Methods PubMed, Web of Science and Embase were reviewed from inception to October 2019 ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…While physical activity (PA) has long been associated with a reduced risk of mortality and morbidity from chronic and degenerative diseases [16][17][18][19][20][21], the research interest on the role of PA on mental health has emerged more recently. PA has been related to an improvement in general well-being [22], enhanced perception of quality of life [23,24] and mood, as well as to a significant reduction in anxious and depressive symptomatology [25].…”
Section: Introductionmentioning
confidence: 99%
“…While physical activity (PA) has long been associated with a reduced risk of mortality and morbidity from chronic and degenerative diseases [16][17][18][19][20][21], the research interest on the role of PA on mental health has emerged more recently. PA has been related to an improvement in general well-being [22], enhanced perception of quality of life [23,24] and mood, as well as to a significant reduction in anxious and depressive symptomatology [25].…”
Section: Introductionmentioning
confidence: 99%
“…A 2016 pooled analysis of ~7000 cases from 11 cohort studies found a hazard ratio of 0.91 (95% CI = 0.83, 1.00) when comparing the 90th and 10th percentiles of cohort‐specific distributions of MVPA, 23 while a related 2019 pooled analysis of ~4000 cases from nine of those 11 cohort studies found engagement in recommended amounts of activity (7.5 to 15 MET‐hours per week) was associated with a ~ 10% lower risk of NHL 4 . Similarly, a 2020 meta‐analysis of 17 cohort and case‐control studies found that participants with the highest levels of physical activity had a 8% lower risk of NHL than those with the lowest levels of physical activity 5 . We found a larger risk reduction (~20%) in the exposure‐response analyses for NHL overall and for each NHL subtypes than in the tertile analysis, and also found that risk began to decrease with relatively low levels of activity.…”
Section: Discussionmentioning
confidence: 98%
“…4 Similarly, a 2020 meta-analysis of 17 studies (nine cohort, eight case-control) reported an overall NHL risk reduction of 8% when comparing high vs low physical activity levels. 5 Conversely, a 2019 meta-analysis of five cohort studies found no association between physical activity and NHL risk. 6 NHL includes a highly heterogeneous collection of subtypes with considerable differences in genetics, biology, aetiology and outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review underlines that (a) higher level of physical activity seems to be inversely associated with lymphoma development (compared to the lower PA level); (b) female subjects appear to better benefit from higher PA levels than boys (Davies et al, 2020). At the same time, a large percentage of adolescents and young adult cancer survivors (AYACs) do not meet the lifestyle guidelines and recommendations for PA, BMI, and/or smoking, involving several late effects and/or comorbidities (Bøhn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%